Study of Phosphate Solubilizing Fluorescent Pseudomonas Recovered from Rhizosphere and Endorhizosphere of Aloe barbadensis (L.). Issue 4 (3rd April 2023) - Rai, Anuradha; Sharma, Naveen Kumar; Singh, Vinod Kumar; Dwivedi, Brahma Swaroop; Singh, Jay Shankar; Rai, Pradeep Kumar
Abstract: Phosphorus (P) is a key nutrient required by plants for their growth and development. A large part of applied phosphatic fertilizer becomes unavailable due to its fixation in soil. In rhizosphere, fluorescent Pseudomonads are instrumental in phosphate solubilization. We isolated Pseudomonads from the rhizosphere of Aloe barbadensis (L.), and screened them for their plant growth promoting ability such as - solubilization of phosphate, auxin production and 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity. A total of 307 fluorescent Pseudomonas were isolated and screened, of which, 24 isolates showed a strong phosphate solubilizing ability, ranging from 69.71 to 236.73 µg ml −1 . The Indole acetic acid (IAA) production by all 24 isolates varied from 28.44 to 151.99 µg ml −1 . However, 17 isolates produced ACC-deaminase ranging from 8.19 to 10.27 µmol mg −1 h −1 . Analyses of 16S rRNA gene and Pseudomonas- specific genes grouped the isolates in seven different species of fluorescent Pseudomonas . Genotypic analysis based on 16S rDNA-RFLP using restriction enzymes (HaeIII, AluI and MspI) and BOX-PCR generated unique genotype specific pattern. The results suggested that Pseudomonas diversity has no association with microenvironments and the sampling site of the plants. 16S rRNA gene-based diversity indices revealed great diversity among the fluorescent Pseudomonas recovered from the rhizospheric regions of the Aloe . Due to the above plant growth-promoting traits, fluorescent Pseudomonas can be exploited as bio-inoculants for crops, with minimal damage to the environment. GRAPHICAL ABSTRACT: UF0001